Influence of surgery on the pharmacokinetics of tramadol following intravenous administration in dogs - Buhari, S.; Kalthum, H.; Goh, Y.M.; Gan, S.H. (Academic Journal, 2013)
Surgery and anesthesia causes fluctuations in hemodynamics which can lead to subtherapeutic drug levels and usually therapeutic failure, making postsurgical pain management difficult. The influence of surgery and anesthesia on the pharmacokinetics of intravenous tramadol in dogs was investigated. Tramadol (3 mg kg-1) was administered during premedication to female dogs (n = 6) undergoing ovariohysterectomy (Group 1) and to another non-surgery group (n = 6) of female dogs (Group 2) and the pharmacokinetics were compared between the groups. The outcome of this study showed that surgery and anesthesia affected the pharmacokinetics of tramadol, as indicated by a two-fold increase in the elimination half-life (1.10±0.18 h in Group 1 compared to 0.49±0.07 h in Group 2) and a three-fold increase in the area under the curve (770.21±117.76 ng.h mL-1 for Group 1 compared to 117.61±85.16 ng.h mL-1 for Group 2). Clearance was also significantly lower (3.98±0.56 mL min-1 kg-1) in Group 1 than in Group 2 (21.06±9.34 mL kg-1). Serum levels of both interleukin-6 and β-endorphin were increased at 6 and 9 h in the surgery group which further indicates that the rapid metabolism and clearance of tramadol in dogs are correlated with postsurgical pain. Therefore, re-administration of tramadol at 3 h is necessary for pain control. This suggests that surgery has a significant effect on the pharmacokinetics of tramadol in dogs